KONSEP DAN MODEL PEMBELAJARAN TADZKIRAH DALAM PENANAMAN AKHLAK KEPADA ANAK DIDIK UNTUK MEMBENTUK KEPRIBADIAN MANUSIA YANG BAIK - Husaini Husaini (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Tadzkirah learning model is a model of moral cultivation to students with several steps, including; Show Examples, Direct (Give Guidance, Encourage (Give Motivation), Zakiyah (Clean), Continuity (Process of Habituation, Remind, Repetition and Reflection, Organize, Heart-Hepar). the universe and its contents, Responsibility, discipline and independence, Honesty, Respect and courtesy, Compassion, care and cooperation, Confident, creative, hard work, and never give up, Justice and leadership, Kind and humble, Tolerance, and love of peace and unity.